2014
DOI: 10.1002/hep.27175
|View full text |Cite
|
Sign up to set email alerts
|

Saturated free fatty acids induce cholangiocyte lipoapoptosis

Abstract: Recent studies have identified a cholestatic variant of nonalcoholic fatty liver disease (NAFLD) with portal inflammation and ductular reaction. Based on reports of biliary damage, as well as increased circulating free fatty acids (FFAs) in NAFLD, we hypothesized the involvement of cholangiocyte lipoapoptosis as a mechanism of cellular injury. Here, we demonstrate that the saturated FFAs palmitate and stearate induced robust and rapid cell death in cholangiocytes. Palmitate and stearate induced cholangiocyte l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 39 publications
3
58
0
Order By: Relevance
“…Excessive exposure of hepatocytes and cholangiocytes to saturated FAs such as PA triggers ER and oxidative stress, ultimately leading to lipoapoptosis 2 6. Accordingly, we found that PA-treated human cholangiocytes (H69 cells) and parenchymal cells (HepG2 cells) underwent apoptosis (figure 3A).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Excessive exposure of hepatocytes and cholangiocytes to saturated FAs such as PA triggers ER and oxidative stress, ultimately leading to lipoapoptosis 2 6. Accordingly, we found that PA-treated human cholangiocytes (H69 cells) and parenchymal cells (HepG2 cells) underwent apoptosis (figure 3A).…”
Section: Resultsmentioning
confidence: 86%
“…Interestingly, we observed that PA induced the expression of FGF19 in H69 cholangiocytes, but not in the hepatic parenchymal cell line HepG2. This response could represent a protective autocrine/paracrine loop to avoid cholangiocyte lipoapoptosis,6 similar to the upregulation of FGF19 in biliary epithelial cells in response to excessive BA concentrations 36 48 49 . FGF19 gene expression seems to be differentially controlled in human biliary cells and hepatocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Cholestatic presentation of NASH has been suggested to develop in a subset of patients [119] and FFAs induce apoptosis not only in hepatocytes but also in cholangiocytes. Indeed, cholangiocyte lipoapoptosis has been shown to occur in high fat-high sucrose-fed mice [117, 120]. Natarajan et al recently found that FFAs induced apoptosis of cholangiocytes through forkhead box O3 (Foxo3)-mediated miR-34a (Fig.…”
Section: Epigenetic Factors and Hepatocyte Lipotoxicity: Novel Targetsmentioning
confidence: 99%
“…In NASH, the primary sources of Hh ligands are the injured hepatic epithelial cells, particularly lipotoxic hepatocytes (Rangwala et al, 2011; Guy et al, 2012) and reactive cholangiocytes (Natarajan et al, 2014; Natarajan et al, 2017). In hepatocytes, fatty acid toxicity provokes ER and apoptotic-stress, resulting in disruption of the cytoskeleton and swelling (a.k.a., ballooning).…”
Section: Physiology Of the Hedgehog Pathway In The Livermentioning
confidence: 99%